2018
DOI: 10.1111/1759-7714.12818
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of combined icotinib and pemetrexed in EGFR mutant lung adenocarcinoma cell line xenografts

Abstract: BackgroundThe combination of EGFR tyrosine kinase inhibitors (TKIs) and chemotherapy is thought to increase treatment efficacy in non‐small‐cell lung cancer (NSCLC). This study investigated the efficacy and potential mechanisms of different combined modes of icotinib plus pemetrexed in EGFR‐mutant lung adenocarcinoma cell line xenograft models.MethodsNude mice were subcutaneously injected with EGFR‐mutant human lung adenocarcinoma cells (HCC827) and randomized into six treatment groups. Tumor xenograft volumes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…The NEJ005 study compared a concurrent regimen and a sequential alternating regimen for the combination of gefitinib and chemotherapy [10,11]. Our in vitro studies suggested that the sequential administration of pemetrexed followed by icotinib exerted a synergistic effect on EGFR-mutant human lung adenocarcinoma cell lines [16], and that the volume and weight of tumor xenografts in the sequential pemetrexed followed by icotinib group were significantly smaller than sequential icotinib followed by pemetrexed group [14]. Therefore, we used an intercalated regimen for combined treatment with icotinib and chemotherapy.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…The NEJ005 study compared a concurrent regimen and a sequential alternating regimen for the combination of gefitinib and chemotherapy [10,11]. Our in vitro studies suggested that the sequential administration of pemetrexed followed by icotinib exerted a synergistic effect on EGFR-mutant human lung adenocarcinoma cell lines [16], and that the volume and weight of tumor xenografts in the sequential pemetrexed followed by icotinib group were significantly smaller than sequential icotinib followed by pemetrexed group [14]. Therefore, we used an intercalated regimen for combined treatment with icotinib and chemotherapy.…”
Section: Discussionmentioning
confidence: 84%
“…However, no studies have investigated whether first-line treatment with icotinib and chemotherapy in combination can improve the PFS and OS for advanced lung adenocarcinoma patients with sensitive EGFR mutations. An in vitro study reported that icotinib and pemetrexed can have a synergistic effect on cancer cells [14]. The present study was designed to investigate whether icotinib combined with chemotherapy (carboplatin/ pemetrexed) can prolong PFS and OS in previously untreated patients with advanced lung adenocarcinoma and sensitive EGFR mutations and to explore the safety of this combination therapy.…”
Section: Introductionmentioning
confidence: 99%
“…Although preclinical and clinical researches have explored the interaction of first-generation EGFR-TKIs and cytotoxic agents [10, 17–23], to date there are no data on preclinical combination of chemotherapy with third-generation EGFR-TKIs, such as osimertinib. The tolerability of osimertinib monotherapy indeed may allow for the development of more efficacious combination regimens.…”
Section: Discussionmentioning
confidence: 99%
“…The study was designed to evaluate the effect of intercalation therapy with ge tinib or erlotinib or osimertinib with platinumar add pemetrexed chemotherapy.Our rst generation target group includes ge tinib,erlotinib.The study demonstin relation to PFS, and OS.Toxicity pro les were generally clinically tolerabled. In another studies are same [19][20][21][22][23][24],the sequence-dependent synergism between platinumar add pemetrexed and ge tinib was demonstrated in human lung cancer cell lines with both wild-type and mutant EGFR genes [25].In this trial, the patients who received a combination of ge tinib with carboplatinpemetrexed showed a statistically signi cant bene t in survival (PFS of 20.90 vs 11.20 months, p < 0.001 and OS of 52.20 vs 38.80, p < 0.013 for ge tinib and carboplatin/pemetrexed and for ge tinib alone, respectively).Several later phase I/II clinical studies showed that an intercalated regimen of chemotherapy and EGFR TKI were safe and effective [26][27][28]29].WSW clinical studies reported that the intercalated regimen offered superior e cacy compared to chemotherapy or EGFR TKIs alone [30,31]. In a three-arm phase II study,The combination was suggested as a new treatment option for patients with unknown EGFR status in a previous clinical study [30],Although molecular tests are used routinely in clinical practice, EGFR status remains unknown in certain patients.We think that the intercalated strategy could be effective in patients with wild-type or unknown EGFR status.According to several clinical studies, Intercalated treatment might be a promising approach for patients with lung adenocarcinoma with EGFR mutant disease or selected patient with unknown EGFR mutation status, [31][32].…”
Section: Discussionmentioning
confidence: 99%